NMR studies on polyphosphide Ce6Ni6P17. (January 2016) - Koyama, T; Yamada, H; Ueda, K; Mito, T; Aoyama, Y; Nakano, T; Takeda, N
Abstract: We report the result of 31 P nuclear magnetic resonance (NMR) studies on Ce6 Ni6 P17 . The observed NMR spectra show a Lorentzian-type and an asymmetric shapes, reflecting the local symmetry around each P site in the cubic unit cell. We have identified the observed NMR lines corresponding to three inequivalent P sites and deduced the temperature dependence of the Knight shift for each site. The Knight shifts increase with decreasing temperature down to 1.5 K, indicating a localized spin system of Ce6 Ni6 P17 . Antiferromagnetic correlation between 4 f spins is suggested from the negative sign of the Weiss-temperature.